EXPLORING THE IMPACT OF STUDENT-CENTERED LEARNING ON ACADEMIC ACHIEVEMENT AND STUDENT MOTIVATION: A REVIEW OF PEDAGOGICAL AND PSYCHOLOGICAL RESEARCH - Elmuradova Dilnoza Shuhrat qizi (Zeta Repository, 2023)
In recent years, student-centered learning has gained popularity as an alternative approach to traditional teacher-centered education. The focus of student-centered learning is on the individual learner, with an emphasis on active engagement, collaboration, and inquiry-based learning. This approach has been shown to have a positive impact on academic achievement, as well as on motivation and engagement. In this article, we will explore the impact of student-centered learning on academic achievement through both pedagogical and psychological approaches.